Estimated Intake of Potassium, Phosphorus and Zinc with the Daily Diet Negatively Correlates with ADP-Dependent Whole Blood Platelet Aggregation in Older Subjects - Karolczak, Kamil; Guligowska, Agnieszka; Sołtysik, Bartłomiej K.; Kostanek, Joanna; Kostka, Tomasz; Watala, Cezary (Nutrients, 2024)
The aggregation of blood platelets is the pivotal step that leads to thrombosis. The risk of thrombotic events increases with age. Available data suggest that minerals taken with diet can affect the course of thrombosis. However, little is known about the relationship between platelet aggregability and mineral intake with diet among elderly people. Thus, we evaluated the associations between the reactivities of platelets to arachidonic acid, collagen or ADP and the estimated quantities of minerals consumed as a part of the daily diet in 246 subjects aged 60–65 years (124 men and 122 women). The found simple (not-adjusted) Spearman’s rank negative correlations are as follows: 1. arachidonate-dependent aggregation and the amounts of potassium, zinc, magnesium, phosphorus, iron, copper and manganese; 2. collagen-dependent aggregation and the amounts of potassium, phosphorus, iron and zinc; and 3. ADP-dependent aggregation and the amounts of potassium, phosphorus and zinc. The negative associations between ADP-dependent platelet reactivity and the amount of potassium, phosphorus and zinc and between collagen-dependent aggregability and the amount of phosphorus were also noted after adjusting for a bunch of cardiovascular risk factors. Overall, in older subjects, the intake of minerals with diet is negatively related to blood platelet reactivity, especially in response to ADP. Diet fortification with some minerals may possibly reduce the thrombotic risk among elderly patients.